Let’s Talk About Sex: Tyrolean Online Study on Reproductive Health Issues - Hosa, Hanna; Böttcher, Bettina; Schatzl, Valentina; Gahl, Mirjam; Weigel, Bettina; Riedl, David; Reiser, Elisabeth; Mariacher, Petra; Toth, Coco; Toth, Bettina (Geburtshilfe und Frauenheilkunde, 2023)
The way pupils and university students talk about sex does not reflect their real understanding of reproductive health issues. Therefore, we developed a survey for pupils and students in Tyrol, Austria, to evaluate the current state of knowledge.Two questionnaires with 39 items for pupils (n = 369) and 53 items for university students (n = 537) were developed, and an online survey was carried out in Tyrol, Austria, between April and July 2022. A sum score for each correct answer to ten identical items in both questionnaires was used to compare groups (range: 0–11 points), with analysis performed using independent sample t-test, analyses of variance (ANOVAs) and chi-square test.With regards to reproductive health issues and fertility awareness, female vs. male participants (p < 0.001), university students vs. pupils (p < 0.001) and medical students vs. other students (p < 0.001) had greater knowledge. Participants who had already had sexual intercourse showed a broader knowledge of contraception and fertility (p < 0.001).The age at which the decline of female fertility becomes relevant was misstated by the adolescents, who gave a mean age of 42.6 years compared to university students who asserted a mean age of 35.9 years (p < 0.001). Overall, the lowest rate of correct answers was found with respect to emergency contraception (30.7%), while knowledge of contraceptive methods was comparatively high (99.2%).Substantial lack of knowledge of reproductive health issues exists, with differences found between pupils and university students, between genders, and according to field of study. Future health and fertility awareness programs at school and university should focus on gender-specific aspects to prevent unplanned pregnancies, sexually transmitted diseases, and childlessness.
Keywords: contraception; female health issues; reproductive health; fertility awareness; family planning